The transformation of technical-tactical behaviors for hand techniques used in attacking below the belt after the 2010 International Judo Federation rule revision - Ito, K.; Hirose, N.; Nakamura, M.; Maekawa, N.; Tamura, M.; Hirotsu, N. (Archives of Budo, 2013)
Background and Study Aim: Due to a 2010 rule revision, attack with the arms or hands below the belt is prohibited, with the penalty being hansoku-make for the first offense. This strict rule must have affected competitors` technical-tactical behaviors with regards to using hands and arms below the belt in contests. The purpose of the present study is to clarify the transformation of technical-tactical behaviors for hand techniques attacking below the belt in men`s contests before and after the 2010 rule revision. Material and Methods: 436 men`s contests from the 2009 Grand Slam Tokyo and the 2010 Grand Slam Paris were examined. DVDs of the Federation of All Japan Judo were used. Five hand techniques used in below the belt maneuvers as referenced in the Kodokan manual were investigated. The analysts unanimously decided if the techniques performed by competitors could be categorized within one of the five hand techniques studied. Results: Use of kibisu-gaeshi significantly decreased (p<0.05). Use of sukui-nage used in countering an opponent`s cross-guard grab significantly increased (p<0.05). Use of kata-guruma not utilizing below the belt hand or arm grabbing significantly increased (p<0.01). German, English, and Japanese contestants significantly decreased in their use of hand techniques below the belt (p<0.01, p <0.05, p<0.05, respectively). Conclusion: Sukui-nage was increasingly used to counter the opponent`s use of the cross-guard grab; the kata-guruma technique underwent a style transformation. On the other hand, kibisu-gaeshi could not be used effectively with the rule revision.